Automatic quality inspection system for discrete manufacturing based on the Internet of Things. (October 2021) - Chen, Bingsheng; Chen, Huijie; Li, Mengshan
Highlights: The main purpose of this research is to use the Internet of Things technology to design an automated quality inspection system. This article uses IDEF modeling technology to propose a discrete manufacturing workshop production line configuration method. This method uses a set of structured two-dimensional relationship tables. Abstract: With the development of information technology and the wide application of embedded technology and automatic detection technology, the requirements for equipment productivity and production process stability are also increasing. The purpose of this research is to use Internet of Things technology to design an automated quality inspection system for discrete manufacturing MESs and analyse its performance. In this study, a manufacturer's inspection system is used as the research experiment object. The products are checked and scanned one by one, and defective products with quality problems are found and returned to the production workshop. The experimental results show that the number of failures detected by the MES quality inspection system is reduced from 150 s to 79 s. This shows that the functions of the MES automated quality inspection system are significantly improved over traditional systems. Graphical abstract: This article aims at the production quality inspection of small and medium-sized discrete manufacturing enterprises. Image, graphical abstract